Antibiotic prescriptions in French day-care centres: 1999–2008. Issue 11 (18th July 2011) - Dunais, Brigitte; van Dijken, Christophe; Bruno, Pascale; Touboul, Pia; Carsenti-Dellamonica, Hélène; Pradier, Christian
Abstract : Objective: Trends in antibiotic prescriptions among children attending day-care centres (DCCs) were studied before and after campaigns promoting prudent antibiotic use and the introduction of pneumococcal conjugate vaccine. Design and setting: Cross-sectional studies were conducted on a two-stage cluster sample of children aged 3 months to 4 years attending DCCs the Alpes Maritimes in France between January and March in 1999, 2004 and 2008. Antibiotic treatments given in the previous 3 months and their indications were studied. Interventions: A local public health intervention promoting prudent paediatric antibiotic prescriptions was implemented in 2000 and followed by a nationwide campaign in 2002. Main outcome measures: Trends in the number and type of antibiotic prescriptions, and indications for antibiotic use, over the study period. Results: 217, 254 and 279 children provided information in 1999, 2004 and 2008, respectively. The proportion of children who had received antibiotics within the previous 3 months fell from 58.5% (95% CI 51.7% to 65.2%) in 1999 to 29.7% (95% CI 24.4 to 35.5) in 2008. The number of treated episodes/child dropped from 0.99±1.14 to 0.35±1.16 (p<0.00001). Otitis media accounted for an increasing percentage of antibiotic use, rising from 35.3% (95% CI 29.0% to 42.2%) to 56.0% (95% CI 46.3% to 66.6%). Prescriptions for third‑generation cephalosporins increased from 26.0% (95% CI 20.4% to 32.5%) to 49.5% (95% CI 39.2% to 59.7%). Conclusions: Paediatric antibiotic prescriptions dropped significantly following campaigns and the introduction of pneumococcal immunisation in France. Improvements are still needed regarding indications and choice of compounds.